Open Educational Resources (OER) dan Penerapannya pada Perpustakaan Institut Agama Islam Negeri Curup - Rahmat Iswanto (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
This paper examines the concept of open educational resources developing in the world of education and libraries and the application of OER development research results to the IAIN Curup library. The problems were how the limitations of the OER and the models developed were, how was the development carried out by the IAIN Curup library, and how the application of the OER model developed in the IAIN Curup library was applied. The method used in this scientific paper is to explain the OER concept based on several sources, both articles and books. Another method is to describe the results of interviews with research subjects related to the application of OER at the IAIN Curup library. The results are a conceptual framework generated from some articles and books as well as an assessment of the application of OER in the IAIN Curup library. The form of OER service is a form of business development to provide the role of information providers in the world of education which must always be maintained and developed by educational institutions by utilizing technology. Meanwhile, the application of OER in the IAIN Curup library is still not optimal due to several constraints both internally and externally.